Effects of school connectedness on the relationship between child maltreatment and child aggressive behavior: A mediation analysis. (February 2023) - Wang, Yao; Ahn, Haksoon; Rose, Roderick A.; Williams, Kimberly
Abstract: Background: Children growing up in a vulnerable and unstable family environment including child maltreatment, poor family functioning, and low social-economic status, are at higher risk of developing undesirable behavioral outcomes compared to peers in the general population. School life plays a critical role during the development of adolescents. Objective: The purpose of this study is to examine the role of school connectedness in the relationship between child maltreatment and aggressive behavior. Participants and setting: This study employed the Fragile Family and Child Well-being Study – Year 15. The final analytic sample size is 2285 families. Methods: Mediation analyses were conducted to evaluate the impact of CPS on child aggressive behavior mediated by school connectedness using OLS regression with robust standard errors. The bootstrap was used to estimate the standard error of the indirect effect. Results: The total effect of CPS contact on child aggressive behaviors was 0.14 (p < .001). The direct effect of CPS contact on child aggressive behavior was 0.13 (p < .001). The indirect effect, that school connectedness significantly mediated the relationship between CPS and child aggressive behavior, was tested and found statistically significant (Coef. = 0.01, p < .05). Conclusions: Findings of the mediation model suggest that interventions targeted at improving school connectedness among adolescents involved in the child welfare system may promote positive outcomes by reducing aggressive behaviors among youth growing in fragile families. On-going trainings are needed for schoolteachers and social workers to better engage adolescents with child maltreatment at school.